The influence of personalization on consumer satisfaction: Trends and challenges - Casaca, L.; Miguel, L. (Data-driven marketing for strategic success, 2024)
In today's digital age, where consumers are inundated with a barrage of information and choices, the ability to tailor marketing efforts to individual preferences has become a powerful tool. This study aims to understand how personalization can influence consumer satisfaction. To achieve this goal, the authors carried out a systematic review of the literature, based on 79 articles published in the WoS™ database between 2014 and 2023. The R-Tool “Biblioshiny for Bibliometrix” was used to perform a comprehensive bibliometrics analysis, based on evaluative and relational bibliometrics techniques, which allow them to analyze the knowledge structure in terms of three different structures: conceptual, intellectual, and social. They concluded that personalization has emerged as a cornerstone of modern marketing strategies, reshaping the way businesses connect with their customers. The impact of personalization on customer satisfaction is profound, leading to enhanced customer experiences, increased engagement, improved customer retention, and the building of trust and credibility.